CHARACTERIZATIONS OF FUZZY STANDARD ELEMENT IN FUZZY LATTICES - Khubchandani, P; Khubchandani, J (TWMS journal of applied and engineering mathematics, 2025)
In this paper, we introduce the concepts of fuzzy neutral elements, fuzzy join-standard, and fuzzy meet-standard elements in fuzzy lattices. Also, we have proved the fundamental characterization theorem of fuzzy join-standard elements in fuzzy lattices. Moreover, we introduce the concepts of [[nabla].sub.F]-standard elements in fuzzy lattices. Further, we have studied the relationship among the fuzzy join-standard, [[nabla].sub.F]-standard, fuzzy meet-distributive, and fuzzy atom in fuzzy lattices. Also, we have introduced the notion and notation of fuzzy p-element in the fuzzy lattice. Keywords: Fuzzy lattices, fuzzy distributive pair, fuzzy semi-distributive pair, fuzzy standard element, [[nabla].sub.F]-standard element, fuzzy p-element AMS Subject Classification: 03B52, 03E72, 06D72